Initial teacher training to promote health and well-being in schools – A systematic review of effectiveness, barriers and facilitators. (October 2016) - Shepherd, Jonathan; Pickett, Karen; Dewhirst, Sue; Byrne, Jenny; Speller, Viv; Grace, Marcus; Almond, Palo; Roderick, Paul
Objectives: To conduct a systematic review of effectiveness, and barriers and facilitators, of initial teacher training to promote health and well-being in schools. Design: Systematic review of the literature. Method: A total of 20 bibliographic databases were searched, including MEDLINE, EMBASE and the Social Science Citation Index. Studies were included if they reported research into the processes and/or outcomes of initial (pre-service) teacher training to promote health. Results: A total of 20 studies met the inclusion criteria, mainly from the UK and Australia. Twelve studies assessed outcomes, commonly using uncontrolled before and after assessment designs. Sixteen studies evaluated the processes of training. Training was diverse in terms of content, format and health topics. The studies demonstrated short-term increases in trainee teachers' factual knowledge of health issues, a general increase in teachers' confidence to teach about health and to identify and help children with specific health issues. There was an increase in teachers' positive beliefs about their role in promoting children's health. None of the studies assessed changes in pupil outcomes. The training was generally considered acceptable and adequate by trainee teachers. However, some of the trainees felt that they still lacked knowledge and confidence to address sensitive health issues on entering teaching practice. Conclusion: This systematic review identified some evidence for the effectiveness of teacher training for health and highlighted factors which facilitate and inhibit effective training. Further evaluation, using controlled trial designs with long-term follow-up of teacher and pupil outcomes, may enable teachers to effectively address the health and education needs of school pupils.